A rasch analysis of the employee’s acceptance towards corporate culture value Akhlak in Indonesian state-owned enterprises - Resista Vikaliana; Antoni Ludfi Arifin; Taufan Maulamin; Sriyani Sriyani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to determine employee acceptance of the corporate culture values of AKHLAK in BUMN, especially PT Pegadaian. The instrument used is a questionnaire based on the Theory of Resources Based View/ RBV and Theory of Planned Behavior/ TPB. The Rasch modeling was used with a survey method and a cross-sectional 2020 study time approach. The survey was conducted on 362 respondents who were drawn by quota sampling. The results of the analysis show a value of +1.58 logit, which is above the average logit item (+0.00 logit). These results indicate the respondent's agreement on employee acceptance of the corporate culture values of AKHLAK. The score that is most difficult to agree on by the respondents in the instrument on the questionnaire given is the 54th item, namely